2002
DOI: 10.1093/embo-reports/kvf221
|View full text |Cite
|
Sign up to set email alerts
|

Arf, Arl, Arp and Sar proteins: a family of GTP‐binding proteins with a structural device for ‘front–back’ communication

Abstract: Arf proteins are important regulators of cellular traffic and the founding members of an expanding family of homologous proteins and genomic sequences. They depart from other small GTP-binding proteins by a unique structural device, which we call the 'interswitch toggle', that implements frontback communication from the N-terminus to the nucleotide binding site. Here we define the sequence and structural determinants that propagate information across the protein and identify them in all of the Arf family prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
282
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 297 publications
(295 citation statements)
references
References 35 publications
9
282
0
3
Order By: Relevance
“…As predicted from sequence signatures, 22 structural studies of Arf-like and Arf-related GTPases, including Golgi Arl1, 74,75 cilium Arl3 76,77,78 and Arl6 79 and endoplasmic reticulum Sar1 80,81 have now shown that autoinhibition by the N-terminal extension and the interswitch takes place in these GTPases and is released by the displacement of the N-terminus and the toggle of the interswitch. Thus, the allosteric mechanism that uses the displacement of the N-terminal extension as a priming event to autoinhibition release and the remodeling of the interswitch as the means whereby information is propagated to the nucleotide-binding site is probably general to the entire Arf-like family.…”
Section: Regulation Of Bacterial Arfgefs By Membranesmentioning
confidence: 80%
See 1 more Smart Citation
“…As predicted from sequence signatures, 22 structural studies of Arf-like and Arf-related GTPases, including Golgi Arl1, 74,75 cilium Arl3 76,77,78 and Arl6 79 and endoplasmic reticulum Sar1 80,81 have now shown that autoinhibition by the N-terminal extension and the interswitch takes place in these GTPases and is released by the displacement of the N-terminus and the toggle of the interswitch. Thus, the allosteric mechanism that uses the displacement of the N-terminal extension as a priming event to autoinhibition release and the remodeling of the interswitch as the means whereby information is propagated to the nucleotide-binding site is probably general to the entire Arf-like family.…”
Section: Regulation Of Bacterial Arfgefs By Membranesmentioning
confidence: 80%
“…With crystal structures depicting the GDP/GTP cycle of Arf1 10,11,14 and Arf6, 20,21 we realized that this spectacular conformational switch is a common feature that defines Arf and Arf-like GTPases as a distinct GTPase family and that it is encoded in specific sequence signatures. 22 This mechanism has the hallmarks of allostery: it allows interactions on the side of the GTPase where it interacts with membranes to propagate information to the opposite side of the protein where it binds guanine nucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…However, because of the amino acid substitutions discussed above, fewer contacts with the bound guanine nucleotide are observed [7][8][9] and the nucleotide is not covered by the G2 (switch I) domain [7,8]. Interestingly, a portion of the extended Gem Cterminus makes contacts with the core G-domain, reminiscent of that seen with the N-termini of GDP-bound Arf proteins [8,16] and the C-terminus of Ran [17]. This combination of structural alterations likely results in the lower GTP/GDP affinity found for RGK proteins when compared to Ras [4,8].…”
Section: Rgk Structurementioning
confidence: 99%
“…[26][27][28] Cloning and characterization of Arl8b was further carried out by Sebald and co-workers who identified Arl8 in a clone-screen from a fetal cartilage cDNA library. 29 Arl8 is a primitive GTPase that appeared early during evolution and has been highly conserved from protozoans to metazoans as well as in plants (Fig.…”
Section: Introductionmentioning
confidence: 99%